PEMBELAJARAN BERBASIS INKUIRI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Izzatul Yazidah; Edy Bambang Irawan; I Made Sulandra (Jurnal Kajian Pembelajaran Matematika, 2020)
21st century human competence is creativity and innovation, communication and collaboration, as well as critical thinking and problem solving. Critical thinking skills need to be possessed by students. Students who have the ability to think critically will tend to respect and respect others. These characteristics are very important for future generations to live in the modern world. One learning that is expected to be able to train and improve critical thinking skills is inquiry-based learning. Inquiry-based learning is a learning process by formulating questions, processing ideas, exploring and evaluating information, analyzing data, and finding relationships and conclusions. Inquiry-based learning emphasizes the process of thinking critically and analytically to seek and find their own solutions to a proposed problem. Inquiry-based learning involves students actively seeking answers to questions or problems. In this case the writer refers to the inquiry training developed by Richard Suchman. The existence of inquiry-based learning is expected to motivate and direct learning that is oriented towards increasing critical thinking skills.